Political Will terhadap Kelembagaan KPK Era Presiden Jokowi - Muhammad Ilham Akbar (Syntax Idea, 2021)
President Joko Widodo's political will will greatly determine the slowness and speed of the Corruption eradication commission. The problems raised in this research are, first, how Is The political will towards the KPK Institution during the era of President Jokowi. Second, how should President Joko Widodo's political will towards the KPK institutions be? This study aims to find and formulate the necessity of President Joko Widodo's political will for the sustainability of the KPK institutions. The legal research method used in this study is a normative juridical research method, based on primary and secondary legal materials. This study concludes that the political will of President Joko Widodo towards the KPK institutions is still far from what is aspired to. President Joko Widodo's political will should be realized in the form of policies that support the strengthening of the KPK Institution.